Comments on the evaluation of massless scattering - Cardona, Carlos; Kalousios, Chrysostomos [UNESP] (Springer Nature, 2016)
The goal of this work is threefold. First, we give an expression of the most general five point integral on ℳ0,n (Formula Presented.) in terms of Chebyshev polynomials. Second, we choose a special kinematics that transforms the polynomial form of the scattering equations to a linear system of symmetric polynomials. We then explain how this can be used to explicitly evaluate arbitrary point integrals on ℳ0,n (Formula Presented.). Third, we comment on the recently presented method of companion matrices and we show its equivalence to the elimination theory and an algorithm previously developed by one of the authors.
Keywords: Field Theories in Higher Dimensions; Scattering Amplitudes